2018
DOI: 10.3371/csrp.kebe.070415
|View full text |Cite
|
Sign up to set email alerts
|

Blood Draw Barriers for Treatment with Clozapine and Development of a Point-of-Care Monitoring Device

Abstract: Survey results demonstrate physicians' desire for point-of-care monitoring technology, particularly among younger prescribers. Prototype sensor results identify that CLZ can be detected and integrated for future device development. Future development will also include integration of WBCs for a complete detection device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…As illustrated in Figure 1a, the challenge to clinicians is that serum clozapine levels cannot be adequately controlled by dosage because of variabilities in drug metabolism (Couchman et al, 2013; Rajkumar et al, 2013; Rostami-Hodjegan et al, 2004). A recent survey indicated that clozapine would be more broadly prescribed if serum levels could be rapidly measured at the point-of-care (POC) to provide clinicians with the timely information required to adjust dosages (Kelly et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure 1a, the challenge to clinicians is that serum clozapine levels cannot be adequately controlled by dosage because of variabilities in drug metabolism (Couchman et al, 2013; Rajkumar et al, 2013; Rostami-Hodjegan et al, 2004). A recent survey indicated that clozapine would be more broadly prescribed if serum levels could be rapidly measured at the point-of-care (POC) to provide clinicians with the timely information required to adjust dosages (Kelly et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Psychotic fears and feelings, such as the fear of being fleeced or the denial of suffering from any psychotic illness at all, can interfere with and hamper regular blood sampling in the more severely affected inpatient population. Making the blood sampling procedure easy in its execution and in its accessibility can contribute to greater patient compliance .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Some of this stems from the challenge of coordinating laboratory, pharmacy, and clinic visits and the extra time required to monitor laboratory results. 10 The fractured nature of community care amplifies these challenges. Clinician reluctance also stems from clozapine’s medical risks, especially agranulocytosis.…”
Section: Introductionmentioning
confidence: 99%